2000
DOI: 10.1007/pl00008673
|View full text |Cite
|
Sign up to set email alerts
|

Rapid systemic accumulation of transcripts encoding a tobacco WRKY transcription factor upon wounding

Abstract: An immediate-early, transiently activated wound-responsive gene was identified in tobacco by fluorescent differential display screening. The full-length cDNA encodes a polypeptide of 356 amino acids with a relative molecular mass of 39,082 Da. The deduced amino acid sequence shows two characteristic features; a leucine-zipper motif found in the more N-terminal region and a WRKY domain containing a zinc-finger motif located in the central region. The gene was designated as wizz (wound-induced leucine zipper zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(150 citation statements)
references
References 40 publications
3
142
0
5
Order By: Relevance
“…Among the WRKY proteins reported so far, only a subset of members, such as ABF2, WIZZ, PcWRKY4, and PcWRKY5, have putative Leu zippers (Rushton et al, 1995;Eulgem et al, 2000;Hara et al, 2000;Cormack et al, 2002). Function of the Leu zipper has been proposed to mediate dimerization and increase the DNA-binding affinity of WRKY proteins (Cormack et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the WRKY proteins reported so far, only a subset of members, such as ABF2, WIZZ, PcWRKY4, and PcWRKY5, have putative Leu zippers (Rushton et al, 1995;Eulgem et al, 2000;Hara et al, 2000;Cormack et al, 2002). Function of the Leu zipper has been proposed to mediate dimerization and increase the DNA-binding affinity of WRKY proteins (Cormack et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2). GaWRKY1 exhibited high sequence identities (41%-45%) to Group IIa WRKY proteins, including PcWRKY4 of parsley (Cormack et al, 2002), AtWRKY18 of Arabidopsis , and Wizz of tobacco (Hara et al, 2000). Alignment of these protein sequences revealed that the WRKY domain, putative Leu zipper, nuclear localization site, and a C-terminal Ala-rich stretch were strictly conserved; outside these regions, however, there was little sequence conservation ( Fig.…”
Section: Isolation Of Gawrky1mentioning
confidence: 97%
“…There are considerable reports on several WRKY transcription factors being induced by cold, salinity or wounding. 9,10,11 Besides the WRKY another superfamily of transcription factors in plants are the MYBs. In plants the MYB transcription factors contains R2 and R3 domains and the binding sequence varies from four to 14 nucleotides.…”
Section: Wrky and Myb Cis Regulatory Elementsmentioning
confidence: 99%
“…Recently, the plant-specific transcription factors, WRKY family proteins containing highly conserved WRKY domain [44], have been found to be involved in the regulation of plant defense response. It has been shown from a number of plants that WRKY genes are rapidly induced by pathogens, pathogen elicitors, or SA treatment [45][46][47]. Arabidopsis WRKY transcriptional factor (AtWRKY52), containing a LRR motif of TIR-NBS-LRR subclass R gene products, has been shown to enhance disease resistance to several strains of Ralstonia solanacearum [48].…”
Section: Introductionmentioning
confidence: 99%